IMPLEMENTASI KEBIJAKAN PEMERINTAH KABUPATEN POLEWALI MANDAR DALAM PROGRAM PELESTARIAN PERAHU SANDEQ - Sunarti Sunarti; Rustan IR; Muchlis Hannan (Journal Peqguruang: Conference Series, 2025)
Local wisdom is the nation's cultural heritage, wisdom. The aim of this research is to find out how the Polewali Mandar Regency Government Policy is Implemented in the Sandeq Boat Preservation Program. The steps and methods used to obtain data are qualitative descriptive research. Research location at the Polewali Mandar Regency Education and Culture Service, and the Polewali Mandar Regency Youth, Sports and Tourism Office. Data collection techniques use observation, interviews and documentation methods. Data analysis techniques with data reduction stages, data presentation, and drawing conclusions. Based on the results of research on the Implementation of Polewali Mandar Regency Government Policy in the Sandeq Boat Preservation Program, the implementation of this policy not only involves technical and administrative aspects, but also requires active participation from the local community to ensure the long-term sustainability of the Sandeq boat preservation program. The sandeq boat preservation program is an important initiative to preserve the unique cultural heritage in West Sulawesi Province, especially in Polewali Mandar Regency. Sandeq boats are a type of traditional boat used by the Mandar people who live on the Pesisir coast. It is hoped that the results of this research can support efforts to preserve sandeq boats in a sustainable manner, ensuring that this valuable cultural heritage can be enjoyed by future generations.